Systematic Review of Factors Related to PM2.5 Exposure on the Risk of Type 2 Diabetes Mellitus - Salma, Rifka Putri; Fitria, Laila (UI Scholars Hub, 2024)
Diabetes mellitus is a major public health problem in many countries, and most of them are type 2 diabetes mellitus (T2DM). Air pollution is thought to contribute to the T2DM incidence, and one of the most important pollutants is PM2.5. This study aimed to determine factors related to PM2.5 exposure and individual factors in increasing the risk of T2DM based on a systematic review. The PRISMA was used as a method of data collection and selection. Of 176 relevant articles identified and screened, 12 articles from various countries published in 2013-2021 were synthesized in this study. Results showed that long-term PM2.5 exposure, high PM2.5 concentrations, and living in densely-populated areas, close to roads, and in areas with industrial activity could increase the risk of T2DM. Population with an older age (>40 years) and a BMI of overweight or obese were more vulnerable. However, men and persons who stopped or never smoked were also at higher risk; thus, further studies need to be carried out along with other risk factors. A future study is recommended to determine the effects of PM2.5 exposure on the incidence of T2DM in Indonesian populations.